2022
DOI: 10.1038/s41598-022-12938-3
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of microRNA-96-5p is associated with adolescent idiopathic scoliosis and low bone mass phenotype

Abstract: Bone densitometry revealed low bone mass in patients with adolescent idiopathic scoliosis (AIS) and its prognostic potential to predict curve progression. Recent studies showed differential circulating miRNAs in AIS but their diagnostic potential and links to low bone mass have not been well-documented. The present study aimed to compare miRNA profiles in bone tissues collected from AIS and non-scoliotic subjects, and to explore if the selected miRNA candidates could be useful diagnostic biomarkers for AIS. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Moreover, some of them were already known for their involvement in cell signaling pathways that controlled the pluripotency of stem cells, such as the Wnt/β-catenin pathway [ 22 ]. Other studies compared data from differentially expressed miRNAs on bone tissues with the plasma levels of the selected miRNAs candidates, to develop a composite diagnostic model for AIS [ 50 ]. Overexpression of miR-151a-3p in primary osteoblasts from severe AIS patients negatively affected bone homeostasis, and the high plasma expression levels suggested miR-151a-3p as a potential biomarker for severe AIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some of them were already known for their involvement in cell signaling pathways that controlled the pluripotency of stem cells, such as the Wnt/β-catenin pathway [ 22 ]. Other studies compared data from differentially expressed miRNAs on bone tissues with the plasma levels of the selected miRNAs candidates, to develop a composite diagnostic model for AIS [ 50 ]. Overexpression of miR-151a-3p in primary osteoblasts from severe AIS patients negatively affected bone homeostasis, and the high plasma expression levels suggested miR-151a-3p as a potential biomarker for severe AIS.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Zang et al also showed a significant negative correlation between circulating miR-145 levels and serum sclerostin, osteopontin, and osteoprotegerin in AIS [ 26 ]. As shown by Chen et al, the analysis of differentially expressed miRNAs in AIS bone and plasma samples represents a new source of biomarkers and actors in the aetiopathogenesis of AIS; for example, miRNA profiles in bone tissues from AIS and healthy controls identified the upregulation of miR-96-5p, which was further confirmed in plasma samples from AIS girls compared to HC [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a model was constructed using plasma miR‐96‐5p levels and patient‐specific parameters (age, weight, and years since menarche), which increased the AUC to 0.752. Furthermore, the original pathway analysis indicated a functional relationship between the bone metabolism pathway and miR‐96‐5p (Chen et al, 2022).…”
Section: Research On Bmsc‐mediated Ais Pathogenesismentioning
confidence: 99%
“…miR-151a-3p could be used as a biomarker to predict severe AIS. In 2022, Chen et al evaluated four patients with severe AIS and four age-matched controls ( Chen et al, 2022 ); in this study, they extracted intraoperative iliac spine bone tissue for RNA microarray analysis. miR-96-5p expression was significantly higher in patients with AIS.…”
Section: Non-coding Rnamentioning
confidence: 99%